Word Formation of Slang Words Found in Looper Movie - Sasa, Trisnafitria Putri; Zaim, M. (Universitas Negeri Padang, 2021)
The purpose of this research is to identify the dominant types of word-formation process of slang words found in the Looper movie script. The type of this research is descriptive research. This research used the theory about word-formation by Mattiello (2008) and Yule (2010). In the finding, the researcher found five types of slang word-formation processes in the Looper movie script. They were blending, clipping, coinage, compounding, and variation. The researcher found 12 slang words with blending type (25.53%), 9 slang words with clipping type (19.14%), 12 slang words with coinage type (25.53%), 6 slang words with compounding type (12.76%), and 8 slang words with variation type (17.02%). The most dominant type of slang word-formation in the Looper movie script is blending and coinage.Key words: Language variation, slang word, word formation